(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of liquidity and capital structure on profitability in food and beverage subsector companies listed on the Indonesia Stock Exchange. The study uses a quantitative approach with an associative approach. The sample consisted of five companies selected using purposive sampling during the 2021–2025 period, resulting in 25 observational data. Liquidity was measured using the Current Ratio (CR), capital structure using the Debt to Equity Ratio (DER), and profitability using Return on Assets (ROA). Data analysis was conducted through classical assumption tests, multiple linear regression, coefficient of determination, and partial and simultaneous hypothesis tests. The results show that CR has no significant effect on ROA, while DER has a significant effect on ROA. Simultaneously, CR and DER have a significant effect on ROA. These findings indicate that capital structure plays a more dominant role than liquidity in influencing the profitability of food and beverage subsector companies.